The Influence of Workload, Job Stress, and Work Spirit on Employee Performance at PT Victory International Futures Surabaya - Yustina Murni; Dian Ferriswara; Galuh Ajeng Ayuningtiyas; Liling Listyawati (Jurnal Manajemen Kewirausahaan dan Teknologi, 2025)
This study aims to examine the effects of workload, job stress, and work spirit on employee performance at PT Victory International Futures Surabaya, a financial services company operating in the highly demanding futures trading industry. Employing a quantitative descriptive–correlational approach, data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression using JASP and Partial Least Squares–Structural Equation Modeling (PLS-SEM) using WarpPLS, which is suitable for addressing multicollinearity issues and relatively small sample sizes (n = 37). The findings reveal that workload and job stress have significant negative effects on employee performance, whereas work spirit has a significant positive effect and emerges as the most dominant predictor. These results reinforce the Job Demands–Resources (JD–R) theory, which posits that job demands such as workload and stress can reduce performance when not balanced with adequate psychological resources like work spirit. Practically, the study recommends that management optimize workload distribution, implement stress management strategies, and strengthen employee motivation to improve performance sustainably. The study is limited by its small sample size and single-company focus, suggesting that future research should expand the organizational context and incorporate additional variables such as job satisfaction or organizational commitment.